Efektivitas Ketersediaan Layanan Fisioterapi di Puskesmas Bukit Indah Kecamatan Muara Papalik Kabupaten Tanjung Jabung Barat Provinsi Jambi - Ucu Suherman; Felix Kasim; Tati Murni Karokaro (Universitas Baiturrahim, 2023)
Availability of physiotherapy services at puskesmas to facilitate access to physiotherapy services for people who are indicated to need general physiotherapy services by prioritizing maintenance through promotive and preventive approaches. This study describes the problems related to the Effectiveness of the Availability of Physiotherapy services at the Bukit Indah Health Center, Muara Papalik District, Tanjung Jabung Barat Regency in terms of Input, Process and Output. This study uses a qualitative descriptive approach, an attempt to present facts about the effectiveness of the availability of physiotherapy services at the puskesmas. The data source for this research is primary data and secondary data. Data collection techniques in the form of observation, interviews, analysis techniques used. The results of the study show effectiveness in terms of input, human resources are in accordance with standards, room facilities, tools and funds are not yet available, patients who require physiotherapy services are included in the top 10 diseases at the puskesmas. In terms of the physiotherapist process, they have been involved in running the service program but are still integrated with other programs. In terms of output, the availability of physiotherapy services at the Bukit Indah Health Center has been felt by the community in the work area of the Health Center, but the types of services still need to be improved. The results of this study can be transferred to health centers that have the same characteristics.